46.3k views
5 votes
1

(1)/(m - n) - \frac{m + n}{m {}^(2) - n {}^(2) }


2 Answers

2 votes

Answer:

0

Explanation:

We need to simplify the given expression . The given expression is ,

→ 1/ ( m - n) - (m + n)/ ( m² - n² )

→ 1/ ( m - n) - ( m + n)/(m+n)(m-n)

  • Using a² - b² = (a+b)(a-b)
  • Now cancel m+n in numerator and denominator .

→ 1/( m - n) - 1/ ( m - n)

→ 0

Hence the required answer is 0 .

User Pygmy
by
8.0k points
3 votes

Answer:


(1)/(m - n) - \frac{m + n}{m {}^(2) - n {}^(2) }

Factor if necessary:

x²-y²=(x+y)(x-y) use this formula


(1)/(m - n) - \frac{m + n}{ {(m + n)(m - n)}}


(1)/(m - n) - \frac{1}{ {(m - n)}}

Take lcm and subtract:

=0

User Garry Shutler
by
7.3k points